Modified Z-plasty of the Patellar Ligament with Reinforcement of the Quadriceps Tendon in the Treatment of Patella Baja - Costa, Tiago António Almeida Orange; Bernardes, Francisco; Miradouro, José; Pereira, Joana; Barreira, Pedro; Carvalho, João (Revista Brasileira de Ortopedia, 2024)
Patella baja is an infrequent knee pathology, but it is limiting due to joint stiffness and localized pain in the anterior region of the knee. It may occur after trauma, prolonged immobilization or local surgical intervention. The striking pathological finding is the shortening and increase in thickness of the patellar ligament. Several surgical techniques have been described for its treatment, and there is no standardized treatment. We describe the case of a 73-year-old female patient who presented with knee stiffness, significant functional deficit, and patella baja after total knee arthroplasty. She underwent a recently described soft tissue surgical procedure, with excellent functional evolution, improving from a Lysholm Knee Score of 16 to 81 points, allowing early mobilization and return to daily life activities.
Keywords: arthroplasty, replacement, knee; knee joint; patella; patellar ligament; tendons